Effectiveness of Ethanol Extract From Sea Pandan (Pandanus Tectorius) on Hydroxyproline Levels as A Parameter For Collagen Formation in The Healing Process of Incision Wounds in Male Rattus Norvegicus - Vanessa Hedyana Putri; Roostantia Indrawati; Andi Abdullah; Afifah Sekarkusuma; Shehnaz Neisa Rasyid (Pelopor Publikasi Akademika, 2026)
This study aims to determine the effectiveness of ethanol extract gel of sea pandan fruit on hydroxycroline levels as a parameter for collagen formation in the healing process of incisional wounds of male white rats (Rattus norvegicus). This study is a laboratory experimental research with a post-test only control group design. The experimental animals used were male white rats which were divided into negative control groups (Gel Base), positive control (Bioplacenton®), and treatment groups with marine pandan ethanol extract gel concentrations of 10%, 20%, and 30%. The treatment was carried out for 10 days at the Integrated Biomolecular and Hyperbaric Laboratory, Faculty of Medicine, Hang Tuah University, Surabaya. The measured parameter was the level of hydroxychlorine of skin tissue. The results showed that there was a significant difference in hydroxyproline levels between treatment groups (p=0.032). The 20% concentration provides the most optimal effect with the highest average hydroxycroline levels and the narrowest data distribution, signaling more consistent fibroblast stimulation and collagen deposition. A concentration of 10% indicates high variability so the effect is less stable, while a concentration of 30% provides a moderate effect that may be affected by mild irritation. The conclusion of this study is that sea pandan fruit ethanol extract gel has the potential to accelerate the healing of incision wounds through increasing hydroxycrolin levels as an indicator of collagen formation.